Muslim Bisexual Religiousness in Indonesia and Singapore (Proceeding of Dakwah Saizu International Conference, 2023)
The life of the Muslim bisexual community is very unique; besides liking the same sex, they are also the opposite sex. One of the reasons why Muslims become bisexual is a psychological impulse, but because religion and society do not accept their existence, they are forced to marry. What is the religion of bisexuals, especially those who are Muslims in Indonesia and Singapore? This article will talk about this.The research method used is phenomenology, with primary data sources obtained through participation action research. The data obtained are in the form of a tick description of the relationship between bisexual behavior and religion as Muslims. The speakers were five (5) people, three from Indonesia and two from Singapore, with criteria: Muslim, over 40 years old, married or had a family, and had been bisexual for at least five years. The results of this study show that bisexual Muslims have contradictory religions; on the one hand, they understand that bisexual behavior is forbidden in Islam, but they have no power to leave it, so even though they are married and have children, they still engage in same-sex relations.